SOSIALISASI PENCEGAHAN KEKERASAN SEKSUAL PADA SMK PGRI 16 JAKARTA - Puspitasari, Anggun Citra Dini Dwi; Rahmawati, Rahmawati; Karyati, Zetty; Kelvin, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The purpose of this community service activity is to provide socialization of sexual violence prevention at SMK PGRI 16 Jakarta. The benefits of this socialization are that students gain insight into acts of sexual violence, and the impacts of sexual violence, and receive assistance in preventing sexual violence and solutions to prevent acts of sexual violence in the school environment. The implementation methods we use are observation, socialization, and evaluation. We provide this socialization by giving a direct understanding of acts of sexual violence, the impacts of sexual violence, and solutions to prevent acts of sexual violence in the school environment. After the socialization, students of SMK PGRI 16 Jakarta showed increased awareness regarding the impacts of sexual violence. They showed positive changes in attitudes regarding the importance of protecting themselves from acts of sexual violence.